Antibacterial Activity Test of Ethanol Extract of Spoon Leaves (Plantago major. L)Against Salmonella typhi - Refaldi Shaputra (Universitas STRADA Indonesia, 2019)
Typhoid is a bacterial infection disease of Salmonella typhi. Conventionally, typhoid treatment is carried out with antibiotics. The irrationality of antibiotics against S. typhi is reported to trigger bacterial resistance, thus requiring an alternative antibacterial agent against typhoid. The diversity of Indonesian medicinal plants is still promising as a potential source of antibacterial agent, including sendok leaf. This study was aimed to determine antibacterial activity of ethanol extract of kacapiring leaves and its fractions against S. typhi. Subsequent fractionation was carried out using liquid-liquid partition method to obtain n-hexane, ethyl acetate, and etanol-water fractions. Antibacterial test was carried out using disk diffusion method to determine the diameter of inhibitory zone at concentrations of 20%, 25%, 30%, and 40%. The best antibacterial activity was revealed by residue fraction of 30% and 40% with inhibition zone diameter of 8,5 ± 0.051 mm and 8,7 ± 0.081 mm, respectively. Sendok have moderate antibacterial activity against S.typhi.